Du bateau au lycée professionnel : les représentations de l'enseignement et de l'apprentissage ouvragées par les enseignants de techniques maritimes - Maryvonne Merri; Sylviane Veillette (Nantes Université, 2014)
One of the missions of the French Maritime Schools is to train future fishermen. Among the teachers at the Maritime School, most of them are former fishermen and/or merchant sailors who have made the transition into teaching. The aim of this paper is to describe the representations of learning and teaching of maritime technology teachers, as well as to further understand the foundation of their representations based on their career, the conditions of their previous apprenticeships (through family, at school, or on the boat), the circumstances surrounding their "migration" towards teaching and the characteristics of their current students. To do so, we gathered the stories of seven former sailors who became maritime technology and navigation teachers. They revealed the conditions of their learning and of their job on the ship, as well as teaching at the Maritime School, which are the circumstances of their consequential career orientation. The maritime technology teachers revealed the main purposes of their activity: to train sailors who follow maritime regulation and acquire maritime knowledge. While often faced with students who have a difficult relationship with school and are occasionally considered as "landsmen", the teachers implement various tools to encourage students to acquire a certain appreciation of the maritime environment, as well as to integrate the various restrictions presented by this environment in the learning process.